On bad intentions and harmful consequences: understanding public perceptions of environmental crime seriousness - Kluin, Marieke (Crime, law and social change, 2025)
The public has grown increasingly concerned about environmental issues. However, few studies examine the perceived seriousness of environmental crimes. Those that do tend to focus on US citizens and compare crime seriousness ratings among different types of crimes, rather than examining the factors that shape perceptions of environmental crime seriousness. By employing a vignette survey among Dutch citizens (N = 261), the current paper seeks to address this knowledge gap. It focuses on two such factors: (1) whether or not the environmental crime is committed intentionally, and (2) whether or not the environmental crime causes considerable harm. The results show that environmental crimes were perceived as more serious when committed intentionally and when they caused considerable harm. Furthermore, intentions affected perceived seriousness less in case of harm and harm affected perceived seriousness less in case the crime was committed intentionally. Together, these findings enhance our understanding of the factors that shape the perceived seriousness of environmental crimes.